The message of Hosea love to the loveless - Kidner, Derek (Leicester, UK IVP, 1981)
Includes bibliographical references.
Copy 1 : "The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990".
Keywords: Bible. O.T. Hosea -- commentaries